Genetic diversity of the entomopathogenic fungus Cordyceps takaomontana in forests and butterfly gardens in Quindío, Colombia (2017)
"In East Asian countries, Cordyceps takaomontana Yakush. & Kumaz is highly valued in traditional medicine as a food ingredient and to strengthen the immune system. This fungus is an entomopathogen that infects pupae or larvae Of lepidopterans. In Colombia it has been reported in non-disturbed tropical rain forests and in butterfly gardens. The aim ofthis research was to describe the morphological and genetic diversity of C. takaomontana in natural and artificial (e.g. butterfly gardens) environments in the department Of Quindío (Colombia) using three nuclear genes (ITS, TEF and RPBI) and morphological traits such as conidia size and synnemata length". -- Tomado del resumen.